Genetic structure of the European hedgehog (Erinaceus europaeus) in Denmark - Rasmussen, Sophie Lund (PLoS One, 2020)
OBJECTIVES: Low genetic diversity can lead to reduced average fitness in a population or even extinction. Preserving genetic connectivity across fragmented landscapes is therefore vital to counteract the negative consequences of genetic drift and inbreeding. This study aimed to assess the genetic composition and consequently the conservation status of a nationwide sample of European hedgehogs (Erinaceus europaeus) in Denmark. METHODS: We applied an adaptation of the genotyping by sequencing (GBS) technique to 178 individuals from six geographically distinct populations. We used a Bayesian clustering method to subdivide individuals into genetically distinct populations. We estimated individual observed (iH(O)), observed (H(O)), and unbiased expected (uH(E)) heterozygosity, inbreeding coefficient (F(IS)), percentage of polymorphic loci (P%) and tested for deviations from Hardy-Weinberg equilibrium (HWE). We used linear models to test for potential anthropogenic effects on the genetic variability of hedgehogs with iH(O), uH(E,) P% and F(IS) as response variables, and assessed the demographic history of the population. RESULTS: The Danish hedgehog population is composed of three genetic clusters. We found a mean P% of 54.44–94.71, a mean uH(E) of 0.126–0.318 and a mean H(O) of 0.124–0.293 in the six populations. The F(IS) was found to be significantly positive for three of the six populations. We detected a large heterogeneity of iH(O) values within populations, which can be due to inbreeding and/or fragmentation. F(IS) values decreased with increasing farmland density, but there was no significant association with human population or road density. CONCLUSIONS: We found a low level of genetic variability and evidence for genetic substructure and low effective population size, which are all consequences of habitat fragmentation. We failed to detect signs of a recent population bottleneck or population increase or decline. However, because the test only identifies recent changes in population size, we cannot reject the possibility of a longer-term decline in the Danish hedgehog population.